The analysis of speed and pressure of wind in rainy weather/Vėjo slėgio ir jo greičio kitimo lyjant analizė - Paukštys, Valdas; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2001)
It is not enough to investigate only the effect of wind on buildings, because deterioration of exterior surfaces of buildings is caused by wind and moisture together. A considerable part of rain gets into the exterior surface of enclosure, penetrates deep down and destroys the material of surface layer. The rain passes through enclosure construction and its surface layer due to wind pressure, through joints of the elements and cracks caused by improper transportation as well as by an inaccurate assembling. At present, new multilayer constructional elements are used for building envelope having numerous assembling seams, therefore, the combined influence of rain and wind becomes rather dangerous. It was established that the wind velocity during the rain is one of the main reasons predetermining moisture penetration into protective-decorative walls made of sand-lime brick with split surface, on concrete-lime mortar, according to the analysis of combined influence of the climate by research data [4]. The total effect of rain and wind on the humidity condition of exterior layers is described. Distribution of real wind velocity was estimated according to the data of the last 10 years. It was found that in Kaunas the average wind velocity increases from 3,4 m/s when the rain is absent up to 4,3 m/s and in Vilnius – the average wind velocity increases from 2,9 m/s when the rain is absent up to 3,7 m/s with an increase of approximately 26%, while in Klaipeda the average wind velocity increases from 3,6 m/s when the rain is absent up to 5,1 m/s with an increase of approximately 42%. On the base of the investigations carried out the suggestion is proposed to use the maximum and mean wind velocity values at the rain for estimating the effect of wind to the moisture behaviour in building elements.Article in Lithuanian.First Published Online: 30 Jul 2012